Marlojong Tradition On The Islamic Law Perspective - Syapar Alim Siregar (Jurnal AL-MAQASID: Jurnal Ilmu Kesyariahan dan Keperdataan, 2022)
This article describes the tradition of marlojong (elopement) perspective of Islamic law. The focus of research in this article is in Padangsidimpuan district of Angkola Julu, Padangsidimpuan, North Sumatra. Marlojong tradition is a marriage performed by a man bringing a woman to his parents' house to be his wife without being known by the female master. Marlojong marriage occurs because the mother of the woman does not give her blessing to her child in choosing a soul mate chosen by her own child. There are some negative impacts for those who do marlojong marriages in the process: For parents, especially parents of women marlojong marriage will get a poor image. Based on the results of the examination, it can be concluded that the practice of marlojong marriage that occurred in Padangsidimpuan Angkola Julu District and carried out by young Muslims Batak Angkola tribe is a practice marriage that is contrary and not in accordance with Islamic sharia. In addition to marlojong marriage has existed from the past and until now still exists, and then this tradition belongs to urf al-fasidah. Urf al-fasidah is a habit carried out by man but contrary to syara‟, legalizing the haram, or rescinding obligations.